Agama dan Kerusakan Ekologi: Mempertimbangkan “Tesis White” dalam Konteks Indonesia - Singgih, Emanuel Gerrit (Faculty of Theology Duta Wacana Christian University, 2020)
Abstract This article is an evaluation of two anthologies which respond to Lynn T. White Jr., who traces the cause of the present ecological destruction to implementation of religious worldviews in the past, and concludes that Christianity as a very anthropocentric religion, is responsible for this destruction. Although the majority of the responders regard that White's article from 1967, which become famous as the